Digital Design of the Customised Cranial Prosthesis - Chen Meng-xia; Guan Tian-min; Shan Li-jun (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Digital design of the customised cranial prosthesis is achieved successfully in this paper based on the standard of medical image CT data from the patient with the DICOM format. DICOM data interface is parsed and three-dimensional cloud point data of defected skull is obtained in VC++6.0 compiler by Visualization Toolkit. Better fitted prosthesis NURBS surface is constructed by analyzing and processing the cloud point data in Geomagic Studio. High quality of the surface is validated by the result of error analysis fully. The three-dimensional solid modeling of the skull prosthesis with smooth shape and high precision is developed by substantiation operations.